Polyethylene Glycol-3350 (Miralax®)+1.9-L sports drink (Gatorade®)+2 tablets of bisacodyl results in inferior bowel preparation for colonoscopy compared with Polyethylene Glycol-Ascorbic Acid (MoviPrep®) - Maqsood Ahmed Khan,; Kevin B. Patel,; Mohammed Nooruddin,; Garth Swanson,; Louis Fogg,; Ali Keshavarzian,; Michael Brown, (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Polyethylene glycol (PEG)-3350, approved by Food and Drug Administration (FDA) only for constipation, combined with 1.9 L of sports drink (SD) (Gatorade®) and bisacodyl (B) is commonly used in outpatient practice for bowel preparation due to cited patient satisfaction and tolerability of this specific regimen. We aim to compare PEG-3350 (Miralax®) with PEG-AA-based (MoviPrep®) in terms of efficacy, patient satisfaction, and the effects of these two regimen on serum electrolytes. Materials and Methods: This study is a prospective, single-blinded, block randomized trial comparing single-dose PEG-3350+SD+B to split-dose 2-L PEG-AA in the outpatient endoscopy unit in patients undergoing colonoscopy. Basic metabolic profiles were checked on the day of randomization and on the day of procedure. Patients completed a survey on the day of procedure. Bowel preparation quality was assessed using the Boston Bowel Preparation Scale (BBPS) by two endoscopists and a nurse present during the procedure. Results: We randomized 150 patients (74 PEG-3350+SD+B and 76 PEG-AA). The PEG-AA group had significantly higher BBPS scores in the right colon by Endoscopist 1, Nurse, and Endoscopist 2 (p 0.005, <0.000, 0.001) and in the left and transverse colon by Nurse and Endoscopist 2 (p 0.004, 0.26, 0.000, 0.006). There was no statistically significant difference in patient satisfaction or change in serum electrolytes between the two groups. Conclusion: Use of single-dose PEG-3350+SD+B results in inferior bowel preparation for colonoscopy compared with split-dose PEG-AA and does not provide any advantage in regards to patient satisfaction. We therefore recommend discontinuing the use of PEG 3350 for bowel preparation.Cite this article as: Khan MA, Patel KB, Nooruddin M, et al. Polyethylene Glycol-3350 (Miralax®)+1.9-L sports drink (Gatorade®)+2 tablets of bisacodyl results in inferior bowel preparation for colonoscopy compared with Polyethylene Glycol-Ascorbic Acid (MoviPrep®). Turk J Gastroenterol 2018; 29: 64-70.